2009
DOI: 10.2527/jas.2008-1424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding high-linoleate safflower seeds on postpartum reproduction in beef cows1,2

Abstract: Two experiments were conducted to evaluate reproductive responses to supplemental high-linoleate safflower seeds in postpartum beef cows. In Exp. 1, 18 primiparous, crossbred beef cows (411 +/- 24.3 kg of BW) were fed Foxtail millet hay starting 1 d postpartum at 1.68% of BW (DM basis) and a low-fat control (control: 63.7% cracked corn, 33.4% safflower seed meal, and 2.9% liquid molasses; DM basis) at 0.35% of BW (n = 9) or a supplement (linoleate) containing 95.3% cracked high-linoleate (79% 18:2n-6) safflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…While many studies have examined the effects of various fatty acid-based supplements on aspects of the reproductive process in dairy cows, there have been few reports for beef cows. Scholljegerdes et al (2009) recorded lower tissue concentrations of LH and IGF-1, follicle numbers, systemic oestradiol and overall conception rate in beef cows supplemented with high-linoleate safflower seeds compared with unsupplemented controls. SimiIarly, Martin et al (2010) observed no advantage of supplementing heifers with soya beans in either productive or reproductive efficiency.…”
Section: Nutritional Effects On Conception and Pregnancy Ratementioning
confidence: 99%
“…While many studies have examined the effects of various fatty acid-based supplements on aspects of the reproductive process in dairy cows, there have been few reports for beef cows. Scholljegerdes et al (2009) recorded lower tissue concentrations of LH and IGF-1, follicle numbers, systemic oestradiol and overall conception rate in beef cows supplemented with high-linoleate safflower seeds compared with unsupplemented controls. SimiIarly, Martin et al (2010) observed no advantage of supplementing heifers with soya beans in either productive or reproductive efficiency.…”
Section: Nutritional Effects On Conception and Pregnancy Ratementioning
confidence: 99%
“…In a previous report, pregnancy rates to TAI or natural service were not influenced by feeding flaxseed or sunflower seeds starting 25 d prior to synchronization with CIDRs and continuing for 50 d (Colazo et al 2004). Furthermore, responses due to supplementation of lipid high in C18:2n-6 has been equivocal with some reporting increased (Whitney et al 2000;Cerri et al 2009;Juchem et al 2010), no difference (Funston et al 2002;Banta et al 2008), or decreased (Alexander et al 2002Ambrose et al 2006;Scholljegerdes et al 2009) reproductive success. This discrepancy in reported responses is likely due to variation in the amount of fatty acid actually reaching specific tissues.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, repression of adipose tissue lipoprotein lipase (LPL) and acetyl-CoA carboxylase (ACC) genes (Travers et al, 1997), with simultaneous up-regulation of the hormone sensitive lipase (HSL) gene (Martin-Hidalgo et al, 1994) would provide the mammary gland with endogenous energy supplies to meet the metabolic demands of lactation. Our laboratory has examined the effects of dietary supplemental fat on body condition score (BCS; 1 = emaciated and 9 = obese; Wagner et al, 1988) and energy partitioning during early lactation in beef cows (Bottger et al, 2002;Lake et al, 2005Lake et al, , 2006aScholljegerdes et al, 2009). Generally, dietary oil supplementation affected tissue fatty acid profile, but effects on biochemical events were not always evident.…”
Section: Introductionmentioning
confidence: 97%